The Role of Artificial Intelligence in Enhancing User Comfort in Health Applications: A Case Study on Aicare - Hasan Mukti Iskandar; Hermawan Yulianto (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The rapid advancement of artificial intelligence (AI) has revolutionized digital healthcare services, particularly through AI-powered health applications such as Aicare. This study examines the impact of AI on user comfort and explores the challenges associated with its implementation. Adopting a qualitative approach, the research involved in-depth interviews with three Aicare users from diverse backgrounds. The study is grounded in the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to analyze the key factors influencing user acceptance of AI-driven healthcare solutions. The findings reveal that efficiency and flexibility are the primary drivers of AI adoption in healthcare applications. However, several challenges persist, including limitations in service personalization, the absence of non-verbal communication, and a lower level of trust in AI compared to traditional face-to-face medical consultations. Furthermore, social and cultural factors significantly influence technology acceptance, with users possessing higher digital literacy demonstrating greater openness to AI-based healthcare services. To enhance user comfort and trust, application developers are encouraged to improve interface design for greater intuitiveness, develop AI systems with enhanced personalization and adaptability, and integrate human-centered interaction features, such as video consultations with healthcare professionals. Additionally, strengthening data security and promoting digital literacy on the benefits of AI in healthcare are crucial for fostering user confidence. With continuous innovation, AI-powered healthcare applications have the potential to become more inclusive and effective solutions for supporting Indonesia’s healthcare system.